Liquid air as an emerging energy vector towards carbon neutrality: A multi-scale systems perspective. (May 2022) - Qi, Meng; Park, Jinwoo; Lee, Inkyu; Moon, Il
Abstract: Liquid air has recently emerged as a new energy vector that has the ability to reserve considerable amounts of renewable energy as both cold and power. Liquid air used for energy storage and transportation has gained increasing attention in both academia and industry, owing to its high flexibility, free availability, and potential high cost-efficiency. Supported by an existing established cryogenic transportation network, liquid air can be an intermediate between conventional fossil fuels and green hydrogen, allowing a smooth and reliable transition towards a 100% renewable energy system. This review offers an overview of previous and emerging liquid air technologies and highlights the potential of liquid air for energy recovery and production from a multi-scale systems perspective (molecular, process, system, and supply chain). Emphasis is placed on how liquid air participates in the current energy system transition and assists in the efficient use and management of both renewable energy and waste energy derived from industries. The review covers a range of technologies, such as air liquefaction and liquid air energy extraction cycles, liquid air energy storage, air separation units, and liquid air supply chains, with a focus on identifying and organizing influential factors to construct energy- and cost-efficient liquid air energy systems. To establish a future liquid air economy, challenges and opportunities are outlined in terms of multi-scale systems design and optimization, liquid air flexibility, and system real-time scheduling and planning to balance power supply and demand while improving the techno-economics for feasible industrial implementation. Highlights: Liquid air recently emerged as an energy vector towards carbon neutrality. Liquid air technologies are reviewed from a multi-scale systems perspective. Liquid air assists in the efficient use of renewables and industrial wasted energy. Challenges and directions are presented to establish a future liquid air economy.